MFG-E8, a clearance glycoprotein of apoptotic cells, as a new marker of disease severity in chronic obstructive pulmonary disease - Zhang,S. (2015)
Milk fat globule epidermal growth factor 8 (MFG-E8) is an opsonin involved in the phagocytosis of apoptotic cells. In patients with chronic obstructive pulmonary disease (COPD), apoptotic cell clearance is defective. However, whether aberrant MFG-E8 expression is involved in this defect is unknown. In this study, we examined the expression of MFG-E8 in COPD patients. MFG-E8, interleukin (IL)-1β and transforming growth factor (TGF)-β levels were measured in the plasma of 96 COPD patients (93 males, 3 females; age range: 62.12±10.39) and 87 age-matched healthy controls (85 males, 2 females; age range: 64.81±10.11 years) using an enzyme-linked immunosorbent assay. Compared with controls, COPD patients had a significantly lower plasma MFG-E8 levels (P<0.01) and significantly higher plasma TGF-β levels (P=0.002), whereas there was no difference in plasma IL-1β levels between the two groups. Moreover, plasma MFG-E8 levels decreased progressively between Global Initiative for Chronic Obstructive Lung Disease (GOLD) I and GOLD IV stage COPD. Multiple regression analysis showed that the forced expiratory volume in 1 s (FEV1 % predicted) and smoking habit were powerful predictors of MFG-E8 in COPD (P<0.01 and P=0.026, respectively). MFG-E8 was positively associated with the FEV1 % predicted and negatively associated with smoking habit. The area under the receiver operating characteristic curve was 0.874 (95% confidence interval: 0.798-0.95; P<0.01). Our findings demonstrated the utility of MFG-E8 as a marker of disease severity in COPD and that cigarette smoke impaired MFG-E8 expression in these patients.